The Existence of Larvul Ngabal Law in the Life of the Kei Community - Nur Aida Kubangun (Különleges Bánásmód)
The legal status of larvul ngabal represents a customary legal system that serves as the fundamental framework governing the social, political, and cultural life of the Kei Islands community. This legal system functions not only as a normative regulatory framework but also as a repository of moral values and a mechanism for conflict resolution that has been passed down through generations. This study aims to examine the contemporary relevance of larvul ngabal within Kei society and explore the ways in which this customary legal system interacts with modern legal frameworks. Employing a qualitative methodology with a historical and cultural analytical approach, this research investigates the role of larvul ngabal law in shaping social structures, resolving conflicts, and preserving customary and cultural values. The findings reveal that larvul ngabal law continues to be a central pillar in maintaining social equilibrium within the Kei community, despite the increasing integration of positive law as part of the formal legal system. The seven principal articles within larvul ngabal law are categorized into three primary legal domains, namely nevnev (criminal law), hanilit (family law), and hawear balwirin (property law). This customary legal framework fundamentally asserts that blood symbolizes life, thereby designating violence and murder as grave offenses that necessitate resolution not only through state law but also through customary legal mechanisms. In instances of disputes or customary law violations, the Kei people predominantly favor resolution through customary legal assemblies rather than formal judicial proceedings, as customary law is perceived to be more culturally congruent and socially integrative. This research contributes to the scholarly discourse on customary law and socio-legal studies, offering insights into the continued significance of indigenous legal systems in fostering social cohesion, regulating communal interactions, and preserving traditional governance structures within indigenous societies at a global level.